Respuesta :
The total energy is an illustration of a composite function.
- The function of total energy is [tex](K + P)(t) = 2.94t^2 -432.4t + 1716[/tex].
- The expression tells the total energy of the falling object.
Given
[tex]v(t) = -9.8t + 24[/tex]
[tex]h(t) = -4.9t^2 + 2t + 60[/tex]
[tex]m =2[/tex] -- the mass of the object
First, we calculate the function of kinetic energy
[tex]K = \frac 12mv^2[/tex]
So, we have:
[tex]K(t) = \frac 12m \times (-9.8t + 24)^2[/tex]
Substitute [tex]m =2[/tex]
[tex]K(t) = \frac 12 \times 2 \times (-9.8t + 24)^2[/tex]
[tex]K(t) = (-9.8t + 24)^2[/tex]
[tex]K(t) = 96.04t^2 - 470.4t + 576[/tex]
The function of potential energy is then calculated as:
[tex]P = 9.5mh[/tex], not 19.5mh
So, we have:
[tex]P(t) = 9.5m \times (-4.9t^2 + 2t + 60)[/tex]
Substitute [tex]m =2[/tex]
[tex]P(t) = 9.5 \times 2 \times (-4.9t^2 + 2t + 60)[/tex]
[tex]P(t) = 19 \times (-4.9t^2 + 2t + 60)[/tex]
[tex]P(t) = -93.1t^2 + 38t + 1140[/tex]
So, the composite function for the total energy is:
[tex](K + P)(t) = K(t) + P(t)[/tex]
[tex](K + P)(t) = 96.04t^2 - 470.4t + 576 -93.1t^2 + 38t + 1140[/tex]
Collect like terms
[tex](K + P)(t) = 96.04t^2 -93.1t^2 - 470.4t+ 38t + 576 + 1140[/tex]
[tex](K + P)(t) = 2.94t^2 -432.4t + 1716[/tex]
The expression tells the total energy of the falling object.
Read more about composite functions at:
https://brainly.com/question/8308119